2002
DOI: 10.1128/jvi.76.14.7094-7102.2002
|View full text |Cite
|
Sign up to set email alerts
|

Novel Endogenous Retrovirus in Rabbits Previously Reported as Human Retrovirus 5

Abstract: Human retrovirus 5 (HRV-5) represented a fragment of a novel retrovirus sequence identified in human RNA and DNA preparations. In this study, the genome of HRV-5 was cloned and sequenced and integration sites were analyzed. Using PCR and Southern hybridization, we showed that HRV-5 is not integrated into human DNA. A survey of other species revealed that HRV-5 is present in the genomic DNA of the European rabbit (Oryctolagus cuniculus) and belongs to an endogenous retrovirus family found in rabbits. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
36
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…The fact that scenarios similar to the XMRV story have been reported before (Griffiths et al, 2002) highlights the need for caution when implying disease causation by a novel virus. The advent of next generation sequencing technologies will increase the likelihood of such reports, as the sheer volume of sequence data generated and sensitivity of the technique makes it more likely that contaminants or non-significant virus sequences will be amplified.…”
mentioning
confidence: 87%
“…The fact that scenarios similar to the XMRV story have been reported before (Griffiths et al, 2002) highlights the need for caution when implying disease causation by a novel virus. The advent of next generation sequencing technologies will increase the likelihood of such reports, as the sheer volume of sequence data generated and sensitivity of the technique makes it more likely that contaminants or non-significant virus sequences will be amplified.…”
mentioning
confidence: 87%
“…The RERV-H family appears to be restricted to the European rabbit because the genomes of related members of the order Lagomorpha, including hares and pikas, do not contain RERV-H (Griffiths et al, 2002). This observation, together with the conservation of open reading frames (ORFs) for gag, pro and pol, indicates that this virus entered the rabbit genome relatively recently in evolution and raises the possibility that it is still active and infectious.…”
Section: Introductionmentioning
confidence: 95%
“…RERV-H was first identified in human tissues by PCR and RT-PCR, and was originally thought to be a novel human retrovirus, denoted human retrovirus-5 (HRV-5) (Griffiths et al, 1997). However, despite having many characteristics of infectious retroviruses, in particular an apparent association with inflammatory diseases and lymphoma (Rigby et al, 1998;Brand et al, 1999;Griffiths et al, 1999;Murovska et al, 2000;Kozireva et al, 2001), cloning of the HRV-5 genome and of some viral integration sites revealed the true origin of this virus and led to its re-designation as RERV-H (Griffiths et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, retroviral sequences (initially designated human retrovirus-5) could be PCR-amplified from various human tissues, but they were ultimately found to represent an ERV of rabbits (15). The possibility that expression of HERVs may contribute to tumors has also been considered.…”
mentioning
confidence: 99%